Wound healing, antidiabetic and antioxidant activity of Neolamarckia cadamba, quercetin rich, extract - Jagat Pal Yadav; Amita Verma; Prateek Pathak; Vikas Kumar; Dinesh Kumar Patel (Pharmacological Research - Modern Chinese Medicine, 2024)
Introduction: Traditional Chinese Medicine (TCM), Neolamarckia cadamba (NMCA), a member of the Rubiaceae family, is well-known for its rich assortment of phytochemicals and has a historical use in addressing various health issues. Quercetin is a bioactive compound that is widely used in botanical medicine and TCM because of its potent antioxidant activity. This study aimed to assess HPTLC analysis and explore the wound healing, antidiabetic, and antioxidant properties of optimized extracts from NMCA stems and bark. The objective of this study was to analyze the metabolites present in the plant and their potential health-related benefits. Methods: The phytoconstituents in NMCA were identified by HPTLC analysis of its ethanolic extracts. The antioxidant activity was assessed using ABTS+ and DPPH assays. Furthermore, potential antidiabetic effects were investigated using inhibition assays targeting α-amylase and α-glucosidase. In addition, the evaluation included an MTT assay (HaCaT cell line) for cell viability and a wound healing scratch assay for cell migration. Result: The ethanolic extract of NMCA was subjected to phytochemical analysis, which revealed the presence of diverse phytoconstituents, including alkaloids, flavonoid phenols, saponins, steroids, glycosides, and tannins. Subsequent HPTLC analysis confirmed the presence of quercetin in the extract. However, the MTT assay indicated the (IC50 313.3 ± 0.091 µg/ml) for NMCA plant extract. The wound healing scratch assay demonstrated significant cell migration. Notably, the ethanolic extract displayed significant antioxidant and antidiabetic activities in a dose-dependent manner. The antioxidant potential was evident in the ABTS+ radical scavenging assay (41.168 %) and DPPH radical scavenging assay, with an (IC50 185.275 µg/mL). Antidiabetic effects were demonstrated through the inhibition of α-amylase (IC50 37.23 ± 1.49 μM) and α-glucosidase (IC50 38.26 ± 1.72 μM). Comparatively, the standard acarbose exhibited (IC50 38.94 ± 0.45 μM) for α-glucosidase and (IC50 34.61 ± 3.71 μM) for α-amylase. Furthermore, the ethanolic extract of NMCA, which is rich in phytoconstituents and quercetin, displayed potent wound healing and antidiabetic and antioxidant properties, suggesting its potential therapeutic significance. Discussion: These results further corroborate the longstanding medicinal use of NMCA, suggesting its therapeutic potential in addressing wound healing, oxidative stress, and diabetes mellitus.